2008
DOI: 10.1007/s00192-008-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

Arcus to arcus microsling: technique and preliminary results

Abstract: Sling procedures have been around for decades in the management of female stress urinary incontinence (SUI), but only in the past decade have they become the preferred technique. The arcus to arcus microsling is an anatomical approach that involves placing a midurethral low-tension tape anchored to the obturator internus muscles bilaterally at the level of the tendinous arc. From February 2005 to July 2006, 20 female patients (mean age=53 years old) with SUI underwent arcus to arcus microsling procedure. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 9 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…Initial prospective and retrospective reports emerged soon after the device was available in 2007 and suggested that the cure rates ranged from about 88%-91.4%. More importantly, these cure rates were consistent with prior TVT and TOT results and were associated with no adverse complications such as pain, dyspareunia, sling erosion, or intraoperative complications [38,39]. In 2010, the first prospective, multicenter, international trial was published by Kennelly et al [40•] and provided prospective follow-up data at 1 year.…”
Section: Resultssupporting
confidence: 62%
“…Initial prospective and retrospective reports emerged soon after the device was available in 2007 and suggested that the cure rates ranged from about 88%-91.4%. More importantly, these cure rates were consistent with prior TVT and TOT results and were associated with no adverse complications such as pain, dyspareunia, sling erosion, or intraoperative complications [38,39]. In 2010, the first prospective, multicenter, international trial was published by Kennelly et al [40•] and provided prospective follow-up data at 1 year.…”
Section: Resultssupporting
confidence: 62%
“…Participants received either the Ophira Mini‐Sling System or the “outside‐in” TOT Unitape T Plus (both Promedon, Argentina). This SIMS involves anchoring a midurethral low‐tension tape into the obturator internus muscles bilaterally at the level of the tendinous arc with no perforation of the obturator membrane through a single vaginal incision under local or regional anesthesia, according to Palma's technique . TOT procedures were performed according to the technique described by Delorme .…”
Section: Methodsmentioning
confidence: 99%
“…A total of 6 studies were conducted in a multicenter setting. Thirteen of the studies described were published in peer reviewed journals; the other studies were either unpublished or not publicly available (Tables 2, 3) [1,[9][10][11][12][13][14][15][16][17][18][19]. Two studies were orally presented at an international conference.…”
Section: Resultsmentioning
confidence: 99%